Pengajaran pendidikan moral Pancasila di Sekolah Menengah Tingkat Atas (SMTA): Suatu Studi Tentang Fungsi Sosialisasi Politik = Teaching of Education on Moral Pancasila at Senior High Schools: A Study on the Function of - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1992)
The leaching of Education Moral Pancasila is given to students. The decision of teaching material is conformed with the government's goal_ It shows that political socialization material has a relationship with the government's goal - legitimacy and nation building of government. Teaching material here means the amount of value, norm, altitude and symbol which are given to students through the teaching of Education Moral Pancasila. This research analyzes the teaching material of education moral Pancasila from the first, second and third volumes of the third edition published in 1985, that was grouped in accord with the order of Pancasila's codes and the group of the supernatural power of Pancasila and the New Order which are out of Pancasila codes. The group of the material is analyzed to find the value, norm, attitude and symbol which are socialized on each group. This research examines the message or value that is given to the students. From those values that are socialized on each group, this analysis is based on the literature and related to the reality in the life of Indonesian government at present time - the material's value is directed to the legitimacy of government or directed to the nation building importance or to the both of them. At last this research tries to conclude that the moral teaching materials can be used effectively to support the political socialization in Indonesia, especially in Primary and political socialization can be used to support the legitimacy of the Indonesian Government.